Endoscopic skull base neurosurgical practice in the United Kingdom. (3rd September 2019) - Alalade, Andrew F.; Venturini, Sara; Dorward, Neil; Thomas, Nick
Abstract: Background: Endoscopic skull base surgery (ESBS) is a new subspecialty area that has become more popular over the past 20 years. It is fast evolving and the indications are getting increasingly diverse. The skill-sets also continue to significantly improve, hence, we, the authors aim to assess the current status of this unique sub-specialty within the United Kingdom. Objective: Our objectives included identifying the proportion of neurosurgeons within the United Kingdom who utilize endoscopic skull base approaches, the background training involved and how much of the overall neurosurgical workload is constituted by endoscopic skull base neurosurgery. There was also a focus on the technical nuances involved with ESBS. Materials and methods: 45 neurosurgeons were included in this study, and a 47% response rate ( n  = 21) was obtained. Results: 7 (33%) had training in ESBS during residency and 8 (38%) had some fellowship exposure to ESBS. Each respondent did an average of 1.9 endoscopic skull base courses prior to commencing their practice. The length of practice ranged from 3 to 15 years (mean - 7.2 years). Although most of the surgeons had mixed sub-specialty interests, the most commonly associated sub-specialty with ESBS was lateral skull base surgery (38%). Conclusion: In the United Kingdom, ESBS appears to be commonly combined with a lateral/open skull base neurosurgical practice. Most of the surgeons had their ESBS training after formal residency. Collaboration with ENT occurs more commonly for extended transphenoidal procedures.